Asparagine endopeptidase-targeted Ultrasound-responsive Nanobubbles Alleviate Tau Cleavage and Amyloid-β Deposition in an Alzheimer's Disease Model. (15th March 2022) - Mi, Xue; Du, Haiqiao; Guo, Xinmeng; Wu, Yan; Shen, Long; Luo, Yukun; Wang, Dekun; Su, Qiuyue; Xiang, Rong; Yue, Shijing; Wu, Songgu; Gong, Junbo; et al.
Abstract: Inhibition of asparagine endopeptidase (AEP) has been implied to be effective for treating tau- and amyloid-beta-mediated neurodegenerative diseases, although a method for targeted intracerebral delivery of AEP inhibitors has not yet been achieved. Here, we fabricated ultrasound-responsive nanobubbles (NBs) to load AEP inhibitor RR-11a, and modified the NB surface with either AEP recognizable peptide AAN or pro-transendothelial transversal motif RGD, i.e. NB(11a)-A and NB(11a)-R, for AEP-targeted treatment of Alzheimer's disease (AD). The developed NBs were uniform, small in size (50.1 ± 1.5 nm), with strong echogenicity and high drug loading efficiency (∼91.97%). When intravenously co-injected in the APP/PS1 mouse model, NB(11a)-R could adhere to endothelial cells and enhance transient opening of the blood-brain barrier (BBB) upon focused ultrasound oscillations, allowing the rest NBs/localized released RR-11a molecules to enter the brain, and then NB(11a)-A could selectively bind with the impaired neurons and deposit RR-11a molecules at the AD lesion. As a result, co-administration of NB(11a)-A and NB(11a)-R significantly promoted accumulation of RR-11a in the mouse brain, and substantially alleviated both tau cleavage and amyloid plaques deposition in the hippocampus. Most strikingly, the cognitive ability of the AD model mice was dramatically improved, achieving a level close to the normal mice. Overall, this unique AEP-targeted nanobubble design provides an efficient intracerebral drug delivery strategy and significantly enhances treatment efficacy of AD. Statement of significance: Asparagine endopeptidase (AEP) is an innovative therapeutic target simultaneously involved in Aβ and tau-mediated Alzheimer's disease (AD) pathology, but targeted delivery of AEP inhibitors has not been achieved yet. Here we developed an efficient strategy to deliver AEP inhibitor RR-11a towards impaired neurons. We fabricated RR-11a-loaded ultrasound-responsive nanobubbles (NBs) and modified the NB surface with RGD peptide to promote BBB crossing upon focused ultrasound oscillations, or with AAN peptide to increase binding of NBs on the neurons. Our results indicated that, co-administration of the NB(11a)-A and NB(11a)-R significantly enhanced accumulation of RR-11a molecules at the AD lesion, alleviated both tau cleavage and amyloid plaques deposition in the hippocampus, and consequently restored cognitive function of the AD model mice. Graphical abstract: Image, graphical abstract